Neuroendocrine control of body fluid homeostasis - McCann,S.M. (2003)
Angiotensin II and atrial natriuretic peptide (ANP) play important and opposite roles in the control of water and salt intake, with angiotensin II promoting the intake of both and ANP inhibiting the intake of both. Following blood volume expansion, baroreceptor input to the brainstem induces the release of ANP within the hypothalamus that releases oxytocin (OT) that acts on its receptors in the heart to cause the release of ANP. ANP activates guanylyl cyclase that converts guanosine triphosphate into cyclic guanosine monophosphate (cGMP). cGMP activates protein kinase G that reduces heart rate and force of contraction, decreasing cardiac output. ANP acts similarly to induce vasodilation. The intrinsic OT system in the heart and vascular system augments the effects of circulating OT to cause a rapid reduction in effective circulating blood volume. Furthermore, natriuresis is rapidly induced by the action of ANP on its tubular guanylyl cyclase receptors, resulting in the production of cGMP that closes Na+ channels. The OT released by volume expansion also acts on its tubular receptors to activate nitric oxide synthase. The nitric oxide released activates guanylyl cyclase leading to the production of cGMP that also closes Na+ channels, thereby augmenting the natriuretic effect of ANP. The natriuresis induced by cGMP finally causes blood volume to return to normal. At the same time, the ANP released acts centrally to decrease water and salt intake.